2016
DOI: 10.18097/pbmc20166205572
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sulodexide on placental mitochondria function in rats with experimental preeclampsia

Abstract: Substitution of drinking water for 1.8% NaCl in pregnant rats caused a pronounced increase in arterial pressure by 24,3% and urinary protein by 117% to day 21 of pregnancy. State 4 respiration of isolated placental mitochondria in the group of negative control was 3- and 1.5-fold higher with malate/glutamate and succinate as substrates than in placental mitochondria isolated from uncomplicated pregnant animals. This led to a decrease of the respiratory control ratio. These results suggest that development of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This could be due to inability of these compounds to penetrate mitochondrial membranes to target mitochondrial mediated oxidative stress. Popova et al reported a reduced blood pressure with improved placental mitochondrial function by sulodexide, an anticoagulant drug, in an experimental rat model of preeclampsia (42). Moreover, a few other studies documented the beneficial effect of selenium in preventing mitochondrial oxidative stress in vitro and in vivo models of preeclampsia (43-45).…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to inability of these compounds to penetrate mitochondrial membranes to target mitochondrial mediated oxidative stress. Popova et al reported a reduced blood pressure with improved placental mitochondrial function by sulodexide, an anticoagulant drug, in an experimental rat model of preeclampsia (42). Moreover, a few other studies documented the beneficial effect of selenium in preventing mitochondrial oxidative stress in vitro and in vivo models of preeclampsia (43-45).…”
Section: Discussionmentioning
confidence: 99%
“…Increases GAGs synthesis [16] and promotes arterial relaxation [80] There are few reports on effective use during pregnancy [81,82]. Decrease in the PE symptoms (lower blood pressure and less proteinuria) in experimental PE in rats [83].…”
Section: Sulodexidementioning
confidence: 99%
“…Normalization of the total capacity of coagulation and fibrinolytic systems in women with autoimmune hyperthyroidism was noted [81], as well as reduction of complications and improvement of perinatal outcomes in women with fetal loss syndrome on the background of thrombophilia [82]. Administration of sulodexide to rats with experimental PE throughout gestation reduced manifestations of the disease: hypertension, proteinuria, and mitochondrial dysfunction in placenta [83].…”
Section: Metforminmentioning
confidence: 99%
“…Further, a study by Chen et al documented reduced Complex IV expression and increased oxidative stress markers in the placenta of a HIF-1α-induced PE mouse model [ 48 ]. Furthermore, utilizing a NaCl rat model of PE, Popova et al demonstrated administering 1.8% NaCl to the pregnant rats increases state 4 respiration and reduces respiratory control ratio in the placental isolated mitochondria [ 49 ].…”
Section: Mitochondrial Dysfunction In Preeclampsiamentioning
confidence: 99%